Climate change awareness in ELT: Ethnography in connected learning and ecojustice pedagogy - Sary Silvhiany; Dedi Kurniawan; Sri Safrina (UPT Bahasa Universitas Tanjungpura, 2023)
This research article explores the integration of climate change education in the context of English as a Foreign Language teacher education. As climate–induced disasters are on the rise, the mitigation of climate change necessitates an interdisciplinary approach to climate education. While science education has extensively addressed climate change education, the field of language education and literacy has not taken drastic measures to participate in climate change education. The article heeds the call for more research on climate change education in second/foreign language and literacy programs. Using the connected learning and ecojustice pedagogy, we engaged 20 preservice teachers in exploring climate change issues within a semester-long creative writing course. Analyses of classroom discussions, reflective writing, and picture book projects showed that the preservice teachers’ awareness of climate change issues developed as they delved into the projects that required their understanding of the global climate issues with the local connection. The article concludes by arguing that connected learning and ecojustice pedagogy support the development of climate change awareness while facilitating preservice teachers’ multimodal writing skills. It recommends that language educators engage in interdisciplinary participation to address climate change issues through curricular engagements that support multimodal-based climate literacy learning.